THE EFFECT OF LEADERSHIP, WORK STRESS AND WORK DISCIPLINE ON EMPLOYEE PERFORMANCE AT THE DPRD SECRETARIAT OFFICE PONOROGO REGENCY - Devy Paramudita Listiani; Umi Farida; Wahna Widhianingrum (International Journal of Economics, Business and Accounting Research (IJEBAR), 2023)
This study aims to determine the effect of leadership, work stress and work discipline on employee performance at the DPRD Secretariat office in Ponorogo Regency. This study uses a quantitative approach. Based on the results of the discussion according to the data managed by the multiple linear regression analysis model it is concluded that; From the results of data analysis it is known that the performance of employees at the Secretariat Office of the DPRD Ponorogo Regency is not affected by the Leadership variable. Employee Performance at the Ponorogo Regency DPRD Secretariat Office and from the results of data analysis it is known that Leadership, Work Stress and Work Discipline simultaneously affect Employee Performance at the Ponorogo Regency DPRD Secretariat Office. Keywords: Leadership, Work Stress, Work Discipline, Employee Performance, DPRD Ponorogo Regency